2012
DOI: 10.1126/science.1215704
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Profiling Shows That miR-430 Reduces Translation Before Causing mRNA Decay in Zebrafish

Abstract: MicroRNAs regulate gene expression through deadenylation, repression and mRNA decay. However, the contribution of each mechanism in non-steady-state situations remains unclear. We monitored the impact of miR-430 on ribosome occupancy of endogenous mRNAs in wild type and dicer mutants lacking mature miR-430. We find that miR-430 reduces the number of ribosomes on target mRNAs before causing mRNA decay. Translational repression occurs before complete deadenylation, and disrupting deadenylation using an internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
614
3
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 667 publications
(661 citation statements)
references
References 36 publications
(54 reference statements)
38
614
3
6
Order By: Relevance
“…In future, it will be important to identify signals in the mRNA 3 0 UTRs and factors that may regulate transition from one silencing stage to another, and thus control the final outcome of miRNA-mediated repression of different mRNAs. During revision of our manuscript, two papers reported that also in zebrafish and Drosophila S2 cells, translational repression precedes mRNA deadenylation and decay [29,30].…”
Section: Translational Inhibition Precedes Poly(a) Tail Shorteningmentioning
confidence: 98%
“…In future, it will be important to identify signals in the mRNA 3 0 UTRs and factors that may regulate transition from one silencing stage to another, and thus control the final outcome of miRNA-mediated repression of different mRNAs. During revision of our manuscript, two papers reported that also in zebrafish and Drosophila S2 cells, translational repression precedes mRNA deadenylation and decay [29,30].…”
Section: Translational Inhibition Precedes Poly(a) Tail Shorteningmentioning
confidence: 98%
“…For the comparison of PAR-CLIP and m 6 A peaks, at least 1 bp overlap was applied as the criteria of overlap peaks. Nonparametric Mann-Whitney U-test (Wilcoxon rank-sum test, two sided, significance level = 0.05) was applied in ribosome profiling data analysis as previous reported [48]. GO term analyses were performed by DAVID [49,50].…”
Section: Sequencing Data Analysismentioning
confidence: 99%
“…Ribosome profiling or Ribo-seq, based on deep sequencing of ribosome-protected mRNA fragments (RPFs), has proven to be powerful in determining ribosome positions and densities across the entire transcriptome [11]. Many research groups have successfully applied Ribo-seq to a wide range of organismal species and reported pervasive pause sites along the coding region (CDS) of mRNAs [12][13][14][15][16][17][18]. From bacteria to human cells, the most consistent pause npg www.cell-research.com | Cell Research sites are located at the start and stop codons, which is in line with the notion that ribosomes tend to pause during initiation and termination [10].…”
Section: Introductionmentioning
confidence: 99%